Indeterminate nodules by the Bethesda system for reporting thyroid cytopathology in Israel: Frequency, and risk of malignancy after reclassification of follicular thyroid neoplasm with papillary-like features. Issue 7 (July 2019) - Rosenblum, Rachel Chava; Shtabsky, Alexander; Marmor, Silvia; Trejo, Leonor; Yaish, Iris; Barnes, Sophie; Yehuda, Moshe; Stern, Naftali; Silman, Zmira; Tordjman, Karen Michèle
Abstract: Objective: We aimed to determine the frequency and risk of malignancy (ROM) for indeterminate thyroid nodules, categories III (B3) and IV (B4) of the Bethesda System for Reporting Thyroid Cytopathology (BSRTC), at a large institution in Israel. Additionally, we investigated the impact of redefining follicular neoplasm with papillary-like nuclear features (NIFTP) as non-malignant on malignancy rates. Methods: In this retrospective study of all thyroid fine needle aspirations (FNAs) performed at Tel Aviv-Sourasky Medical Center between January 2013 and December 2015, we assessed ROM for B3 and B4 nodules. Potential risk factors thought to affect a-priori ROM were assessed. Suspected NIFTP lesions were re-examined, and if proven, reclassified as benign. Results: 3701 nodules were sampled in 2919 FNAs performed on 2674 patients. B3 reports comprised 7.7% of all nodules (n = 284); B4 represented 3.6% (n = 132). In multivariate logistic regression, male gender, being of former Soviet Union origin, and smoking increased ROM for B3 nodules by a factor of 7.97 (P = 0.002; CI: 2.2–23.4), 9.15 (P = 0.021; CI:1.4–60.0), and 11.0 (P = 0.001; CI 2.8–44.8), respectively. Reclassifying NIFTP decreased ROM from 14% to 12.5% for B3, and from 26.7% to 25% for B4 nodules. NIFTP comprised 9.5% of previously diagnosed resected malignant tumors. Conclusions: The relative frequencies of B3 and B4 nodules and their associated malignancy rates were consistent with previous series. Risk factors identified for malignancy may help characterize patients most likely to benefit from surgery. Reclassifying NIFTP had a substantial impact on the ROM in the resected tumors previously diagnosed as malignant.